2016
DOI: 10.31235/osf.io/59m86
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Notice and Takedown in Everyday Practice

Abstract: *Abstract:*It has been nearly twenty years since section 512 of the Digital Millennium Copyright Act established the so-called notice and takedown process. Despite its importance to copyright holders, online service providers, and Internet speakers, very little empirical research has been done on how effective section 512 is for addressing copyright infringement, spurring online service provider development, or providing due process for notice targets.This report includes three studies that draw back the curta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 0 publications
0
52
0
2
Order By: Relevance
“…211 While these examples may seem extreme, in 13.3% of takedown requests in a sample, the underlying infringing content cannot be located, and for another 6%, the allegedly infringed work cannot be identified. 212 Third, the DMCA's notice-and-takedown requirements establish barriers to entry for new competitors because notices from others, by their nature, require repeated investigation. A small company that publishes usergenerated content but has limited resources must dedicate at least some of its staff to responding to takedown requests even though they may turn out to be false.…”
Section: When Notice Liability Is Less Successfulmentioning
confidence: 99%
“…211 While these examples may seem extreme, in 13.3% of takedown requests in a sample, the underlying infringing content cannot be located, and for another 6%, the allegedly infringed work cannot be identified. 212 Third, the DMCA's notice-and-takedown requirements establish barriers to entry for new competitors because notices from others, by their nature, require repeated investigation. A small company that publishes usergenerated content but has limited resources must dedicate at least some of its staff to responding to takedown requests even though they may turn out to be false.…”
Section: When Notice Liability Is Less Successfulmentioning
confidence: 99%
“…Although complaints and redress mechanisms can be helpful, studies have indicated that, if improperly formulated, they may have a "chilling effect" on end-users, who are dis-incentivised from using them to exert their rights. 21 In this regard, it is significant that, as currently formulated, the complaints and redress mechanisms included in art.13 remain very vaguely sketched. It is also worth noting that a Compromise Proposal tabled by the Council is particularly worrying, as it would place decision-making in the case of disputes in the hands of the right holder-a party with strong incentives to disallow use.…”
Section: Question 6-germanymentioning
confidence: 99%
“…Lumen, a project at the Berkman-Klein Center for Internet and Society, acts as a clearinghouse for legal complaints and requests for removal of online materials, and is particularly robust for information such as DMCA takedown requests received by a small number of participating intermediaries. Researchers have been able to make good use of this data to analyze how the notice and takedown system works in practice, and how it is changing over time (Urban et al, 2016;Urban and Quilter, 2006).…”
Section: Transparency Reportingmentioning
confidence: 99%